Cloning and expression of a Vi mimotope of Salmonella enterica serovar Typhi through nucleotide-nucleotide hybridization approach.l - Chua, Kek Heng; Kee, B.; Thong, Kwai Lin (Academic Journals, 2009)
A recombinant His-Vi protein of Salmonella enterica serovar Typhi was successfully constructed and cloned into an expression vector through a nucleotide-nucleotide hybridization approach. After transformation of the construct into Escherichia coli, the recombinant His-Vi protein with a size of approximately 4 kDa was successfully produced and proven by Western blot analysis. This recombinant protein can be used to detect specific anti-Vi antibody produced by typhoid patients. Overall, the His-Vi recombinant protein could serve as a potential diagnostic reagent to detect S. Typhi infection in an individual.